Investigation of the relevant kinetic processes in the initial stage of a double-arcing instability in oxygen plasmas. - Mancinelli, Beatriz; Prevosto, Leandro; Chamorro, Juan Camilo; Minotti, Fernando; Kelly, Héctor (My University, 2018)
A numerical investigation of the kinetic processes in the initial (nanosecond range) stage of the double-arcing instability was developed. The plasma-sheath boundary region of an oxygen operated cutting torch was considered. The energy balance and chemistry processes in the dis charge were described. It is shown that the double-arcing instability is a sudden transition from a diffuse (glow-like) discharge to a constricted (arc-like) discharge in the plasma-sheath boundary region arising from a field-emission instability. A critical electric field value of 107 V/m was found at the cathodic part of the nozzle wall under the conditions considered. The field-emission instability drives in turn a fast electronic-to-translational energy relaxation mechanism, giving rise to a very fast gas heating rate of at least 109 K/s, mainly due to reactions of preliminary dissocia tion of oxygen molecules via the highly excited electronic state populated by electron impact. It is expected that this fast oxygen heating rate further stimulates the discharge contraction through the thermal instability mechanism.
Keywords: Double-arcing.; Oxygen plasmas.; Investigation.